Study of preliminary results of Obamacare: is the healthcare reform efficient? (Economic and Political Thought, 2017)
There is ample evidence of widespread inefficiency in health care systemsin the early 2000s. The article is an attempt to find a balanced view on theefficiency of the Obama Healthcare Reform before it is reshaped by the newadministration and the US Congress. No doubt Obamacare is a unique exampleof a healthcare reform. But is the reform really efficient? According topreliminary results, it achieved its goals to a certain extent, and at the sametime it created a lot of new problems that should be solved. One of them,still open, is the issue of who should be in charge of the regulation of thehealthcare system: to what extent the government should take part in thisprocess; whether the shift from private to public regulation was an effectivestep in the development of the healthcare system; and if a free market shouldtake place in case of such a good as healthcare. Nowadays, Obamacare isa burning topic. During his presidential campaign, Donald Trump notifiedthat he would dismantle and/or restructure the Obama healthcare reform.Whatever the final outcome of his attempts to replace and/or to change theAffordable Care Act is going to be, it is worth assessing the health reform,which has attracted so much attention in the US and the world. The applicationof efficiency concepts to health care systems is a challenging topic, whichraises both theoretical and practical problems. A review of input and outputvariables is carried out in the article. My assumption, which I will try to prove,is that the healthcare system in the USA is too expensive, and as a result it isless effective and, actually, not so ‘affordable’ as it was supposed to be.